External Financial Flows and Domestic Credit Volatility Effect on Industrialization in Selected African Countries - Wushibba Bako (Review of Business and Economics Studies)
Countries all over the world focus on industrialization as a foundation for rapid economic development and unemployment reduction. Without stable external and domestic finance, we cannot achieve this goal. Financial volatility has an impact on a country’s industrialization process. The aim of this study is to determine how external and domestic credit volatility affect industrialization in Africa. Data for some selected countries for 1992–2020 was used. The author used the Prais-Winsten regression method with Panel Corrected Standard Errors (PCSE) to estimate and analyze the model. Descriptive and quantitative methods of analysis were also used to analyze the long-balanced panel data set for the 17 selected African countries with available data. The results showed a combination of positive and negative effects of financial volatility on industrialization in Africa. The study concludes that domestic credit volatility has adversely affected industrialization in Africa and recommends the development of financial institutions on the continent through recapitalization, skilled manpower development and innovative development of different financial instruments.